STUDI KINETIKA PENGERINGAN BUNGA ROSELLA (Hibiscus Sabdariffa) MENGGUNAKAN PENGERING RAK UDARA RESIRKULASI - Rustam Santiko Nugroho; S Suherman (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
This study was performed to determine the most appropriate thin layer drying model and the effective moisture diffusivity of Roselle (Hibiscus sabdariffa) using recirculated tray dryer. Rosella dried using recirculated tray dryer at temperatures of 40, 50 and 60ºC. The drying data were fitted to eleven thin layer models and a thin layer model for the roselle calyx was developed by regressing the coefficients of the best fit model. The newton model was most adequate model for describing the thin layer drying kinetics of the roselle calyx. The drying constant was found to vary linearly with temperature. Also, effective diffusivity was evaluated by using Fick’s second law, which varied from 1.405 x 10-10 to 2.283 x 10-10 m2/s. The dependence of moisture diffusivity on temperature was described by Arrhenius type equation. The activation energy for moisture diffusion during drying was 21.02 kJ/gmol.